2017
DOI: 10.1016/j.jpeds.2016.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Irritable Bowel Syndrome Characteristics Are Related to Both Sex and Pubertal Development

Abstract: Objective To determine the relationship of both pubertal development and sex to childhood irritable bowel syndrome (IBS) clinical characteristics including gastrointestinal symptoms (eg, abdominal pain) and psychological factors. Study design Cross-sectional study with children ages 7–17 years (n = 143) with a pediatric Rome III IBS diagnosis recruited from both primary and tertiary clinics between January 2009 and January 2014. Subjects completed 14-day prospective pain and stool diaries, as well as validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Compared to healthy controls, children with FAPD report higher somatization scores . Although not clear why, girls tend to report more somatic symptoms than boys . Moreover, children with IBS report more somatic symptoms than children with FAP .…”
Section: Fapd and Somatizationmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared to healthy controls, children with FAPD report higher somatization scores . Although not clear why, girls tend to report more somatic symptoms than boys . Moreover, children with IBS report more somatic symptoms than children with FAP .…”
Section: Fapd and Somatizationmentioning
confidence: 86%
“…13,24,28,37,49 Although not clear why, girls tend to report more somatic symptoms than boys. 50 Moreover, children with IBS report more somatic symptoms than children with FAP. 28,29 Furthermore, somatization is an important predictor of outcomes in children with FAPD.…”
Section: Key Pointsmentioning
confidence: 99%
“…Kutatásunk megerősítette azokat a korábbi nemzetközi eredményeket is, amelyek alapján a krónikus fájdalom lányok körében gyakoribb. A jelenség a fájdalomérzékelés és -feldolgozás nemi különbségeivel magyarázható [12][13][14].…”
Section: Megbeszélésunclassified
“…In this volume of The Journal, Chumpitazi et al 12 provide new insights into the role of pubertal maturation and sex in the clinical presentation of childhood IBS. The authors conducted a cross-sectional study with children ages 7-17 years who met pediatric Rome III IBS diagnosis.…”
mentioning
confidence: 99%
“…The authors hypothesized that the interaction is linked to a combination of different sex-specific physiologic responses and personal factors. 15 Chumpitazi et al 12 relied on self-reported Tanner stage as opposed to assessment by a health professional, however, this technique has been reported to correlate with physical examination by a physician and in some instances with hormonal levels. [16][17][18] The phase of the menstrual cycle was not considered in menstruating adolescents, which as discussed influences IBS-pain characteristics.…”
mentioning
confidence: 99%